Lymphedema following axillary lymphnode sampling versus axillary lymphnode dissection for patients with breast carcinoma in Al-Karama Teaching Hospital, Iraq - Saood, Mahmood J.; Abdulla, Mohanad Hamed; Tawfiq, Naser R. (International Surgery Journal, 2017)
Background: Lymphedema is a collection of fluid in some parts of the body. It is common after surgical intervention. Different approaches of dealing with lymphnode involvement in axilla have been describe. The main objective of present study is to determine the prevalence of lymphedema after different methods of axillary lymphadenectomy and axillary sampling techniques in Iraq. Methods: This was a cross-sectional study in which post-operative lymphedema of the operated arm was compared in 25 patients with breast cancer after axillary ALND (the excised node more than 4 lymph node up to 18 node) and 25 patients following axillary ALNS of only enlarged hard lymphnode. Results: The results of post-operative follow up from three months to three years following ALND patients showed significant increase in the arm circumference over those exposed to ALNS of the axilla. Conclusions: It can be concluded that axillary lymphnode sampling of axilla associated with negligible lymphedema compared with ALND the routine performance of axillary dissection should be considered with caution.